Pengaruh penyuluhan bahaya seks bebas terhadap sikap remaja - Indriani, Nova; Putri, Ratna Dewi (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Ikatan Perawat Kesehatan Komunitas Indonesia (IPKKI), 2023)
Background: The sexual behavior practiced by teenagers is recently upsetting. The impacts of their sexual behavior that may happen are the occurrence of sexually transmitted disease, or pregnant and laboring under 21 years. Based on a pre-survey conducted on ten teenagers in relationship status, 80% teenagers assumed that having relationship as a widespread thing. 20% were ready to be responsible with pregnancy consequence whenever it happened. Purpose: This study was to identify the effect of education about free sex dangers toward teenager attitude. Methods: This was a quantitative study with analytical research design and quasi experiment approach occupying one group pretest posttest. This study was conducted since June to July 2019 to investigate the effect of education about free sex dangers toward teenager attitude at Karang Rejo Village of Negeri Katon Sub District of Pesawaran Regency. The population of the study consisted of 223 teenagers in the age of 16 – 19 years old. The random sampling technique resulted 70 people. The data collection was through questionnaires. The data was analyzed by using univariate (mean) and bivariate (T-Test). Results: The result of the study showed the mean score of the teenagers before following counseling about free sex dangers was 66.00 with 14.828 standard deviation. The mean score of the teenagers after following counseling about free sex dangers was 82.20.00 with 11.499 standard deviation. Conclusions: There was an effect of education about free sex dangers toward teenager attitude (t test > t table, 16.200 > 4.197, p value = 0.000 (p value < α =0.05)). Suggestions for teens encourage teens to get along with others that make teens comfortable. Discuss with health workers, related to reproductive health. Encourage young people to take part in organizations that have positive activities such as being active in youth organizations, mosque youth study for Muslims. Keywords : Attitude; Free Sex; Education Pendahuluan: Perilaku seksual yang dilakukan oleh para remaja kita saat ini sudah sampai pada batas yang sangat mengkhawatirkan.Dampak dari aktivitas seksual remaja dalah terkena penyakit menular seksual (PMS), hamil atau melahirkan pada usia kurang dari 21 tahun Dari hasil pra survey 10 remaja yang telah berpacaran, sebanyak 80% menganggap bahwa pacaran merupakan hal yang biasa, sebanyak 20% remaja tersebut mengungkapkan jika memang terjadi kehamilan mereka akan bertanggung jawab. Tujuan: Diketahui pengaruh penyuluhan bahaya seks bebas terhadap sikap remaja. Metode:Jenis penelitian kuantitatif, desain penelitian analitik dengan pendekatan eksperimen kuasi dengan one group pretest-postest yang meneliti tentang pengaruh penyuluhan bahaya seks bebas terhadap sikap remaja di Desa Karang Rejo Kecamatan Negeri Katon Kabupaten Pesawaran waktu penelitian telah dilakukan bulan Juni- Juli tahun 2019. Populasi peneltiian seluruh remaja usia 16-19 tahun berjumlah 233 orang dengan jumlah sampel sebanyak 70 orangdiambilsecara random sampling. pengambilan data dengan kuesioner. Analisis data secara univariat (rata-rata) dan bivariat (t-test). Hasil: Hasil penelitian diketahui rata-rata sikap remaja sebelum diberikan penyuluhan bahaya seks bebas adalah 66,00 dengan estándar deviasi 14,828. Rata-rata sikap remaja sesudah diberikan penyuluhan bahaya seks bebas adalah 82,20 dengan standar deviasi 11,499. Simpulan: Ada pengaruh penyuluhan bahaya seks bebas terhadap sikap remaja (t-test> t tabel, 16,200> 4,197, p- value = 0,000 (p-value < α = 0,05). Saran bagi remaja anjurkan remaja untuk bergaul dengan orang lain yang membuat remaja nyaman. Berdiskusi dengan petugas kesehatan, terkait dengan kesehatan reproduksi. Anjurkan remaja untuk mengikuti organisasi yang mempunyai kegiatan positif seperti aktif dalam karang taruna, pengajian remaja masjid bagi umat muslim. Kata Kunci : Sikap; Seks Bebas; Penyuluhan.